SECULAR GREEK MIGRATION TO RUSSIA of the END OF XVI – FIRST HALF XVII CENTURIES - T. A. Oparina (Vestnik MGIMO-Universiteta, 2017)
The article is devoted to the issue of migration in Russia in the Early-modern time the Orthodox subjects of the Ottoman Empire and its vassal States. It presents the dynamics of migration, the analysis of its causes, revealed the social origins of immigrants, studied the place which they received in Russian society. Found that the Russian government was interested in migration. The Greeks always were readily accepted in Russia and received Russian citizenship. The Russian government was guided by several motives. In the first place, the government proceeded from the doctrine of Moscow as the III Rome. The concept was laid on the Russian Tsar functions of the Byzantine Emperor. After the fall of Byzantium the mission the only Orthodox sovereign ruler – Moscow Tsar, was the defense of Orthodoxy and the salvation of believers. Using Greek migration was implemented a complex of Messianic beliefs about Holy Russia. In addition, the migration was allowed to expand the Russian privileged class for the former nobility of Byzantium, as well as to replenish the ranks of specialists in military affairs. The motives of the resettlement of the Greeks themselves in the first place were religious. The threat of Islamization sounded like the main reason for their desire to stay in Russia. The authorities have always responded to such requests. As a result, Russia moved more than 200 people. The most intensive migration was purchased in periods of close diplomatic relations between the Russian and Greek parties: when adopting an Imperial title, the establishment of the Patriarchate and preparation for the Smolensk war (1632–1634), the Church ritual reforms of Patriarch Nikon. Social origins of immigrants have varied greatly. It was the inhabitants of the Danubian principalities, who were captured by the Tartars; the military rank of the Ottoman army, merchants, artisans, members of the families of the Turkish authorities, landowners, representatives of Byzantine aristocratic dynasties, the relatives of the higher Greek clergy. They all had the opportunity to obtain a recommendation letter of the patriarchs of the Christian East. This document was created by the possibility to obtain the rank of Moscow nobleman. In the period under review, more than two dozen immigrants entered the Czar’s court; seven of them have confirmed the title of Prince. About ten immigrants have become translators of the Diplomatic department. Other immigrants enrolled in the Department for Foreigners serviceman, where from 1630 to 1654 was a special military Greek company. From 1641 to 1672 in Moscow there was a Greek settlement. Greek colonies appeared even in Siberia, for example, in Tomsk. Greek immigrants have influenced the development of Russian society